1995
DOI: 10.1038/377544a0
|View full text |Cite
|
Sign up to set email alerts
|

A role for phosphatidylinositol transfer protein in secretory vesicle formation

Abstract: Vesicular traffic in eukaryotic cells is characterized by two steps of membrane rearrangement: the formation of vesicles from donor membranes and their fusion with acceptor membranes. With respect to vesicle formation, several of the cytosolic proteins implicated in budding and fission have been identified. A feature common to all these proteins is that their targets, when known, are other proteins rather than lipids. Here we report, using a previously established cell-free system derived from a neuroendocrine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
139
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(147 citation statements)
references
References 29 publications
7
139
1
Order By: Relevance
“…Our findings are consistent with the observation that ARF, but not B-COP, is associated with CSVs of hepatocytes [22]. The lack of effect of coatomer depletion in the present modified cell-free system is in agreement with the lack of stimulation of secretory vesicle biogenesis by a coatomer-enriched cytosol fraction in a similar cytosol-dependent cell-free system [23]. Our observations are also in line with the results of a previous study addressing the role of coatomer in vivo, which shows that ~-COP antibodies block membrane transport from the endoplasmic reticulum to the Golgi complex but not from the TGN to the plasma membrane [24].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are consistent with the observation that ARF, but not B-COP, is associated with CSVs of hepatocytes [22]. The lack of effect of coatomer depletion in the present modified cell-free system is in agreement with the lack of stimulation of secretory vesicle biogenesis by a coatomer-enriched cytosol fraction in a similar cytosol-dependent cell-free system [23]. Our observations are also in line with the results of a previous study addressing the role of coatomer in vivo, which shows that ~-COP antibodies block membrane transport from the endoplasmic reticulum to the Golgi complex but not from the TGN to the plasma membrane [24].…”
Section: Discussionsupporting
confidence: 93%
“…Perhaps the Nmyristoylated ARF1 peptide was more potent in eliciting a phospholipase D activation relevant to TGN-derived secretory vesicle biogenesis than the N-myristoylated ARF4 peptide [33]. A role of phospholipase D in the biogenesis of TGNderived secretory vesicles would be consistent with the growing evidence implicating lipid modifications in the course of vesicle budding and fission [23,[34][35][36][37].…”
Section: Discussionmentioning
confidence: 59%
“…Fwd is required for the synthesis of PI4P on Golgi membranes and for the formation of Rab11-and PI4P containing organelles at the cell equator (Polevoy et al, 2009). Because PITPs can stimulate vesicle budding from the trans-Golgi network and also provide vesiculating activity for scission of coatomer-coated vesicles in vitro (Jones et al, 1998;Ohashi et al, 1995;Simon et al, 1998) Gio might be involved in vesicle formation. We found that localisation of Gio and Rab11 to the cleavage furrow in dividing spermatocytes requires the wild-type function of Cog7, indicating that Cog7 might be an upstream component in a gio-Rab11 pathway during cytokinesis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphoinositides are essential in several aspects of membrane traffic [9,10], and PITP has been found to be required. PITP is required for the exocytosis of secretory granules [11,12] and budding of secretory vesicles from the trans-Golgi network [13,14]. Many phosphorylated inositol lipids are synthesized on demand, directly from PtdIns, at different sites in the cell.…”
Section: Introductionmentioning
confidence: 99%
“…This includes both vesicle formation and exocytosis [11][12][13]. Dictyostelium systems have more in common with mammalian systems with regard to their use of phosphoinositides in signalling cascades [35].…”
mentioning
confidence: 99%